Genetically defined favourable adiposity is not associated with a clinically meaningful difference in clinical course in people with type 2 diabetes but does associate with a favourable metabolic profile. Issue 9 (11th February 2021) - Heald, Adrian H.; Martin, Susan; Fachim, Helene; Green, Harry D.; Young, Katherine G.; Malipatil, Nagaraj; Siddals, Kirk; Cortes, Gabriela; Tyrrell, Jessica; Wood, Andrew R; Beaumont, Robin N.; Frayling, Timothy M.; et al.
Abstract: Aims: Change in weight, HbA1c, lipids, blood pressure and cardiometabolic events over time is variable in individuals with type 2 diabetes. We hypothesised that people with a genetic predisposition to a more favourable adiposity distribution could have a less severe clinical course/progression. Methods: We involved people with type 2 diabetes from two UK‐based cohorts: 11, 914 individuals with GP follow‐up data from the UK Biobank and 723 from Salford. We generated a 'favourable adiposity' genetic score and conducted cross‐sectional and longitudinal studies to test its association with weight, BMI, lipids, blood pressure, medication use and risk of myocardial infarction and stroke using 15 follow‐up time points with 1‐year intervals. Results: The 'favourable adiposity' genetic score was cross‐sectionally associated with higher weight (effect size per 1 standard deviation higher genetic score: 0.91 kg [0.59, 1.23]) and BMI (0.30 kg/m 2 [0.19, 0.40]), but higher high‐density lipoprotein (0.02 mmol/L [0.01, 0.02]) and lower triglycerides (−0.04 mmol/L [−0.07, −0.02]) in the UK Biobank at baseline, and this pattern of association was consistent across follow‐up. There was a trend for participants with higher 'favourable adiposity' genetic score to have lower risk of myocardial infarction and/or stroke (odds ratio 0.79 [0.62, 1.00]) compared to those with lower score. A one standard deviation higher score was associated with lower odds of using lipid‐lowering (0.91 [0.86, 0.97]) and anti‐hypertensive medication (0.95 [0.91, 0.99]). Conclusions: In individuals with type 2 diabetes, having more 'favourable adiposity' alleles is associated with a marginally better lipid profile long‐term and having lower odds of requiring lipid‐lowering or anti‐hypertensive medication in spite of relatively higher adiposity.